An analysis of the effect of organizational citizen shipbehavior on internal service quality - Demirel, Yavuz; Karademir, Ömer (National Research University, Higher School of Economics (HSE), 2024)
Organizational citizenship behavior, explained in terms of the concepts of altruism,conscientiousness, sportsmanship, courtesy, and civic virtue, is generally managed in two dimensions: as organizational citizenship behavior towards the individual and towards the organization. Internal service quality, on the other hand, is based on the principle that relations between employees working indifferent units of the organization, or between units, or between the organization and the employee, are conducted according to quality standards. Purpose. Thus, the main purpose of this study is to determine the potential of employees’ perceptions of organizational citizenship to explain internal servicequality. Method. For this purpose, data were collected from 216 public sector employees in X provincein Turkey through a questionnaire. The study first tested the construct validity and reliability of the scales. A structural equation model was established to analyze the research model. Findings. Structural equation model analysis revealed that organizational behavior towards individuals has a positive effecton organization-related, group-related, and person-related internal service quality, while organizational behavior towards the organization has a positive effect on person-related internal service quality. Value of results. From the research results, there is a moderate relationship between organizational citizenship behavior and internal service quality, and perceptions of organizational citizenship behaviorare predictors of internal service quality. From these results, it appears that the psychological sense of ownership, which is critical to employees’ success in the workplace, acts as an influencing factor for their relationships with each other.
Keywords: 8. Economic growth